Ultrasound-Guided Percutaneous Release of A1 Pulley by Using a Needle Knife: A Prospective Study of 41 Cases - Pan, Min; Sheng, Shuya; Fan, Zhiqi; Lu, Hao; Yang, Hong; Yan, Fei; E, Zhansen (Frontiers in Pharmacology, 2019)
Objective The purpose of this study was to evaluate the efficacy of ultrasonography-guided percutaneous A1 pulley release with the needle knife for trigger finger. Methods The prospective study included 21 patients (21 fingers) who underwent blind release with the needle knife and 20 patients (20 fingers) who underwent ultrasonography-guided release with the needle knife. The thickness and width of A1 pulley, clinical grade before and after release, complications, and operation time were compared between the groups. Results The results showed that the ultrasonography-guided group had significantly better grade postoperatively and reached to 100% complete release in one time compared to the blind group (p<0.05). Moreover, no any complications had been happened in the ultrasonography-guided group. A relatively longer operation time of the ultrasonography-guided group was observed compared to the time of the blind group. Conclusions The needle knife is a very good tool for release of triggering fingers. Ultrasound provides a direct and precise visualization of the thickness, width and location of A1pulley lesion. The combined use of ultrasound and the needle knife can achieve the best result for trigger finger. Moreover, the combination changes the traditional opinion and operator-dependent mode that were once widely adopted in the hospital of Chinese Medicine.